Analisis Implementasi Marketplace dan Digital Payment pada Belanja APBN untuk Memberdayakan UMKM - Raharjo, Raharjo (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
The COVID-19 pandemic has caused adversity in various sectors for almost all countries in the world, including Indonesia. The economic sector is one of the ones affected by the pandemic, both the manufacturing sector and the Micro, Small and Medium Enterprises (MSME) sector without exception. The government realizes that MSMEs have unique characteristics in playing their role to support economic development, so integration is very necessary as a facilitator for the realization of financial inclusion and the digital economy. The Ministry of Finance through the Directorate General of Treasury has built an ecosystem in the form of a Government Marketplace and Digital Payments to encourage efficiency, effectiveness, transparency and accountability of state spending, as well as participate in empowering MSMEs. Through the development of online shopping applications that meet the payment rules at the expense of the State Revenue and Expenditure Budget (APBN) and the government's procurement of goods/services, an ecosystem has been built that integrates the existence of work units that use APBN, MSMEs as providers of goods/services, and banks. the state as a platform provider with the Digital Payment application (Digipay). Even though digipay has been designed by taking into account the principle of ease of use, in its development, users still feel a reluctance to transact. This research uses a qualitative method which aims to identify what conditions affect the implementation of the government marketplace from the side of the relevant parties involved in it.